Changes in EC Directives and Impact on Presentation of Financial Statements in the Czech Republic - Marcela Žárová (European Financial and Accounting Journal, 2013)
The EC 4th Directive has been in force since 1978, at least till 2001 without fundamental changes. Nearly the same history concerns the EC 7th Directive, firstly issued in 1983. Then new requirements, such as new disclosures and valuation rules, including provisions on fair value accounting, have been added. Less attention has been paid to considering whether existing requirements could be simplified or removed. Research studies confirm that amendments have tended to ignore the comparability and usefulness of the financial statements, increased reporting requirements and the number of Member State options. All these facts have ultimately, in the long run, led to increased complexity and regulatory burden for all companies. European Commission proposed to simplify the 4th and 7th Council Directives as regards financial information obligations and to reduce administrative burdens, in particular for SMEs. This article investigates impact of new Directives financial reporting requirements on presentation of financial statements of companies those use local regulatory rules, which should comply with the Directive of June 26, 2013 repealing the 1978 and 1983 Directives and their subsequent amendments, in the Czech Republic. Conclusion from this article might be useful for practice as for the potential future changes in presentation of financial statements or researchers who find out similarities or differences between European accounting systems.
Keywords: M41; 650; EC 4th Directive; EC 7th Directive; Administrative burdens; Presentation of financial statements